헵탄의 화원 직경 변화를 고려한 대형콘칼로리미터의 발열량 측정 결과 분석 - 유우준(You, Woo Jun); 남동군(Nam, Dong-Gun); 염문천(Youm, Moon Cheon); 김성찬(Kim, Sung-Chan); 유홍선(Ryou, Hong-Sun) (한국화재소방학회 논문지, 2014)
The present study has been conducted to analyse the effects of various pool diameters on the measurement of heat release rate (HRR) of heptane fire using large scale cone calorimeter (LSC). The burning rate which is the major parameter for HRR compared with the previous model suggested by A. Hamins. The combustion efficiency for heptane by oxygen consumption method is about 91%, which is almost same with the previous results of 92% suggested by J. Gore. The convective HRR by enthalpy consumption method was 54% lower than HRR by oxygen consumption method. This results are practical use for establishing the reliability of heat release rate for fire experiment. 본 연구에서는 대형 콘 칼로리미터(large scale cone calorimeter, LSC)를 사용하여 헵탄 풀 화재(pool fire) 실험에서 화원의 직경 변화에 따른 발열량(HRR) 측정 결과를 정량적으로 분석하였다. 발열량에 중요한 영향을 미치는 연소율(burning rate)은 A. Hamins의 연구 자료에서 제시한 모델링 곡선과 비교하여 정확성을 검증하였으며, 산소 소모법에 의한 연소효율(combustion efficiency)은 이론발열량에 비해서 91% 정도로 J. Gore이 제시한 헵탄의 연소효율 92%와 유사한 것을 확인하였다. 엔탈피소모법에 의한 열손실은 전체 발열량의 54% 정도로 측정부에서 대류 발열량으로 측정되었으며, 본 연구 결과는 화재실험에서 발열량 측정값의 신뢰성 분석(reliability analysis)을 위한 기초 연구 자료로 활용하는데 유용한 정보가 될 것으로 사료된다.